1990
DOI: 10.2307/1591259
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Vaccine Strains and Georgia Field Isolates of Infectious Laryngotracheitis Virus by Their Restriction Endonuclease Fragment Patterns

Abstract: Seven restriction endonucleases (REs) were used to cleave the DNA from seven vaccine strains of infectious laryngotracheitis (ILT) virus and from six Georgia field isolates of ILT virus. After electrophoresis of the resulting RE fragments, the patterns were compared in order to differentiate strains of ILT virus. The six chicken-embryo-origin (CEO) vaccines were identical with each RE, but the tissue-culture-origin (TCO) vaccine strain differed from the CEO vaccines using five of the REs. Four of the six field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 31 publications
0
20
0
4
Order By: Relevance
“…While not formally tested, active excretion of virus in both groups suggests that the challenge strains would transmit readily, as has been previously demonstrated for the SA2 vaccine (Coppo et al, 2012b). Transmission of vaccine strains is important epidemiologically as several outbreaks of ILT have been attributed to revertant vaccine strains (Andreasen et al, 1990;Guy et al, 1990) and recombinant strains derived from vaccine strains (Lee et al, 2012). While most ILTV vaccines are efficacious, many of them possess considerable residual virulence, which can further increase during back passages in chickens (Guy et al, 1991).…”
Section: Discussionmentioning
confidence: 84%
“…While not formally tested, active excretion of virus in both groups suggests that the challenge strains would transmit readily, as has been previously demonstrated for the SA2 vaccine (Coppo et al, 2012b). Transmission of vaccine strains is important epidemiologically as several outbreaks of ILT have been attributed to revertant vaccine strains (Andreasen et al, 1990;Guy et al, 1990) and recombinant strains derived from vaccine strains (Lee et al, 2012). While most ILTV vaccines are efficacious, many of them possess considerable residual virulence, which can further increase during back passages in chickens (Guy et al, 1991).…”
Section: Discussionmentioning
confidence: 84%
“…Early assays were based on RFLP analysis of ILTV genomic DNA (Kotiw et al, 1982;Guy et al, 1989;Andreasen et al, 1990). However, RFLP analysis of genomic ILTV DNA has not been widely used because it is time-consuming and occasionally difficult to interpret results.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have used restriction endonuclease analysis to differentiate various ILTV strains (Andreasen et al, 1990;Guy et al, 1989;Keller et al, 1992;Keeler et al, 1993;Kotiw et al, 1982;Leib et ed., 1986;Sikezdi, 1991). In our study, the divergence found by restriction analysis between subgroups IVa through IVd appears to be more pronounced than the difference between various ILTV strains in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…So far, restriction endonuclease analysis has mainly been used in examination of a limited number of herpesvirus isolates from falcons, pigeons and psittacine birds (Aini et al, 1993), and for differentiation of ILTV strains and isolates (Andreasen et al, 1990;Guy et al, 1989;Keeler et al, 1993;Keller et al, 1992;Kotiw et al, 1982;Leib et al, 1986;Sheppard, 1991;Sikezdi, 1991). In this study, a wide spectrum of herpesviruses isolated from different species of birds was compared for the first time by endonuclease restriction patterns of viral genomic DNA.…”
Section: Introductionmentioning
confidence: 99%